The Impact of COVID-19 on Hospitalised COPD Exacerbations in Malta - Yvette Farrugia; Bernard Paul Spiteri Meilak; Neil Grech; Rachelle Asciak; Liberato Camilleri; Stephen Montefort; Christopher Zammit (Pulmonary Medicine)
Introduction and Aims. The first COVID-19 case in Malta was confirmed on the 7th of March 2020. This study is aimed at investigating a significant difference between the number of acute exacerbations of chronic obstructive pulmonary disease (AECOPD) admissions and their inpatient outcome at Mater Dei Hospital during the COVID-19 pandemic when compared to the same period in 2019. Furthermore, we aim to determine predictors of mortality in AECOPD inpatients. Method. Data was collected retrospectively from electronic hospital records during the periods 1st March until 10th May in 2019 and 2020. Results. There was a marked decrease in AECOPD admissions in 2020, with a 54.2% drop in admissions (n=119 in 2020 vs. n=259 in 2019). There was no significant difference in patient demographics or medical comorbidities. In 2020, there was a significantly lower number of patients with AECOPD who received nebulised medications during admission (60.4% in 2020 vs. 84.9% in 2019; p≤0.001). There were also significantly lower numbers of AECOPD patients admitted in 2020 who received controlled oxygen via venturi masks (69.0% in 2020 vs. 84.5% in 2019; p=0.006). There was a significant increase in inpatient mortality in 2020 (19.3% [n=23] and 8.4% [n=22] for 2020 and 2019, respectively, p=0.003). Year was found to be the best predictor of mortality outcome (p=0.001). The lack of use of SABA pre-admission treatment (p=0.002), active malignancy (p=0.003), and increased length of hospital stay (p=0.046) were also found to be predictors of mortality for AECOPD patients; however, these parameters were unchanged between 2019 and 2020 and therefore could not account for the increase in mortality. Conclusions. There was a decrease in the number of admissions with AECOPD in 2020 during the COVID-19 pandemic, when compared to 2019. The year 2020 proved to be a significant predictor for inpatient mortality, with a significant increase in mortality in 2020. The decrease in nebuliser and controlled oxygen treatment noted in the study period did not prove to be a significant predictor of mortality when corrected for other variables. Therefore, the difference in mortality cannot be explained with certainty in this retrospective cohort study.